Influence of secondary thermal cycle on softening behavior and mechanism of heat affected zone in TIG-welded spray formed 7055 aluminum alloy - Zhengping Lu; Lihua Yu; Junhua Xu; Chengchao Du; Hao Zhang (Journal of Materials Research and Technology, 2022)
In this study, fine position samples of heat affected zone under single and secondary thermal cycles were simulated by heat treatment method. The influence of secondary thermal cycle on softening behavior and mechanism of heat affected zone in TIG-welded spray formed 7055 aluminum alloy were studied. The results showed that the mechanical properties of the solid solution zone decreased after the second thermal cycle. The hardness of the solid solution zone decreased from 180HV to 103HV and the tensile strength decreased from 570 MPa to 346 MPa after the second thermal cycle. The main reasons for the reduction of mechanical properties in the solid solution zone after the second thermal cycle were the weakening of the solid solution strengthening effect and the occurrence of over-aging. After the second thermal cycle in the over-aging zone, the mechanical properties decreased and then increased with the increase of the thermal cycle temperature. The lowest hardness value in the over-aging zone after the second thermal cycle decreased from 124HV to 103HV, and the tensile strength decreased from 410 MPa to 284 MPa. The main reason for the decrease of mechanical properties in the overaging zone after the secondary thermal cycle was the intensification of overaging caused by the coarsening of η phase. Overall, the width of the heat affected zone increased after the secondary thermal cycle, and the most seriously softened area extended toward the fusion line.